How Buddhism acquired a soul on the way to China - Park, Jungnok, 1971-2008 (Oxford Centre for Buddhist Studies monographs., 2012)
How Buddhism Acquired a Soul on the Way to China tells the story of the spread of Buddhist religious thinking and practice from India to China and how, along the way, a religion was changed.